U-shaped association between abnormal serum uric acid levels and COVID-19 severity: reports from the Japan COVID-19 Task Force. (September 2022) - Fukushima, Takahiro; Chubachi, Shotaro; Namkoong, Ho; Otake, Shiro; Nakagawara, Kensuke; Tanaka, Hiromu; Lee, Ho; Morita, Atsuho; Watase, Mayuko; Kusumoto, Tatsuya; Masaki, Katsunori; Kamata, Hirofumi; et al.
Highlights: We analyzed the serum uric acid levels and hyperuricemia in patients with COVID-19. High serum uric acid levels were associated with the requirement of invasive mechanical ventilation. Low serum uric acid levels were also associated with the requirement of invasive mechanical ventilation. Abstract: Objectives: This study aimed to identify the relationship between abnormal serum uric acid levels or a history of hyperuricemia and COVID-19 severity in the Japanese population. Methods: We included 1523 patients enrolled in the Japan COVID-19 Task Force cohort between February 2020 and May 2021. We compared the clinical characteristics, including co-morbidities, laboratory findings, and outcomes, particularly invasive mechanical ventilation (IMV), among patients with and without abnormal uric acid levels or a history of hyperuricemia. Results: Patients with high serum uric acid levels were older and had higher body weight and body mass index than those without. In addition, the multiple logistic regression analysis revealed a significant association between high serum uric acid levels or a history of hyperuricemia and an increased risk of IMV (odds ratio [OR] = 1.77; P  = 0.03/OR = 1.56; P  = 0.04). Moreover, patients with low uric acid levels on admission were also associated significantly with the requirement of IMV (OR = 5.09; P <0.0001). Conclusion: Abnormal serum uric acid levels or a history of hyperuricemia were significantly associated with COVID-19 severity in the Japanese cohort.